2009
DOI: 10.1080/13682820802256965
|View full text |Cite
|
Sign up to set email alerts
|

Gesture and speech integration: an exploratory study of a man with aphasia

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 14 publications
1
50
1
Order By: Relevance
“…Moreover, Records (1994) showed earlier that aphasic patients relied more on visual information provided by referential gestures if auditory information was more ambiguous. On the other hand, Cocks, Sautin, Kita, Morgan, and Zlotowitz (2009) found that the multi-modal gain of a bimodal presentation (gesture and speech) was reduced in a case of aphasia compared to a healthy control group.…”
Section: Visual Exploration Behaviour In Aphasic Patientsmentioning
confidence: 89%
“…Moreover, Records (1994) showed earlier that aphasic patients relied more on visual information provided by referential gestures if auditory information was more ambiguous. On the other hand, Cocks, Sautin, Kita, Morgan, and Zlotowitz (2009) found that the multi-modal gain of a bimodal presentation (gesture and speech) was reduced in a case of aphasia compared to a healthy control group.…”
Section: Visual Exploration Behaviour In Aphasic Patientsmentioning
confidence: 89%
“…Furthermore, gestures facilitate children's comprehension of semantically co-expressive words (McNeill, Alibali, & Evans, 2000;Morford & Goldin-Meadow, 1992). Other studies have shown how adults and children integrate gesture and speech so that each contributes unique information to the unified interpretation (adults: Cocks, Sautin, Kita, Morgan, & Zlotowitz, 2009;Kelly, Özyürek, & Maris, 2010;children: Kelly, 2001;Sekine, Sowden, & Kita, 2015). Unlike the previous studies on children's comprehension of speech-gesture combinations, the current study investigated how children integrate the cohesive use of space in a sequence of gestures with spoken discourse.…”
mentioning
confidence: 99%
“…Therefore, in order to fully understand a speakers' intention, addressees are required to comprehend and integrate information from both the speech and the gesture channels. This psycholinguistic process is be referred to here as gesture and speech integration (Cocks, Sautin, Kita, Morgan, & Zlotowitz, 2009). …”
mentioning
confidence: 99%